2020
DOI: 10.1109/tcsi.2020.2982074
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spectral Degradation and Error Compensation in 5G NR Digital Polar Transmitters

Abstract: Cellular standards evolve to support increasingly higher bandwidths which results in strict in-and out-of-band requirements such as lower error vector magnitude (EVM) and/or adjacent channel leakage ratio (ACLR). Digital polar transmitters, which are showing the best performance in terms of power consumption, are challenged to fulfill these requirements. This work will show that even in case of ideal analog components and infinite digital resources, there are principle limitations in terms of out-of-band noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In terms of power consumption, the digital polar architecture is the most promising transmitter architecture. It has been shown that polar architecture has an inherent power efficiency gain of up to 3 dB compared to the Cartesian architecture, due to the in-phase and quadrature (I/Q) signal summation in the latter [31]. Several successful designs and chip prototypes [32]- [36] have demonstrated the feasibility and superiority of the digital polar transmitters.…”
Section: ) Digital Transmitter Architecturesmentioning
confidence: 99%
“…In terms of power consumption, the digital polar architecture is the most promising transmitter architecture. It has been shown that polar architecture has an inherent power efficiency gain of up to 3 dB compared to the Cartesian architecture, due to the in-phase and quadrature (I/Q) signal summation in the latter [31]. Several successful designs and chip prototypes [32]- [36] have demonstrated the feasibility and superiority of the digital polar transmitters.…”
Section: ) Digital Transmitter Architecturesmentioning
confidence: 99%
“…be the autocorrelation function (ACF) of the output signal which, without further assumptions, depends on both the absolute time t and the time displacement τ . Plugging (6) into (8) results to…”
Section: Mathematical Model Of Dithering Dtc-based Frequency Synmentioning
confidence: 99%
“…Such phase shifters need to be able to operate in the GHz frequency range. Several works describe the construction of circuits capable of doing so, and their spectral effects [3]- [6]. These systems are using a digital input that describes a phase offset or time delay relative to a reference signal.…”
mentioning
confidence: 99%
“…It also enables the whole transmitter to be integrated on a single chip, decreasing system cost and form-factor. In addition, the polar architecture has a power efficiency gain of up to 3 dB compared to the Cartesian, due to the omission of I/Q signal summation [9]. Moreover, a comprehensive analytical study followed by a CMOS implementation of a polar quantizer chip prototype demonstrated the superiority of signal-to-quantization-noise ratio improvement compared to rectangular (I/Q) quantizer [10].…”
Section: Introductionmentioning
confidence: 99%